Investigation of Influencing Factors on the Deformation of Sheet Pile Wall with a Relieving Platform - Ming Zhang; Wei Wang; Ronghua Hu; Ziyi Wang (Advances in Materials Science and Engineering)
Owing to the complexity of the sheet pile wall with a relieving platform, there are a large number of factors that affect the mechanical and deformation characteristics of the wall structure. Moreover, studying the influencing factors on the deformation of the retaining wall is beneficial in the selection of design parameters and deformation control. 28 groups of test models of the retaining wall structure are designed to analyze the effect on the deformation of rib pillars and determine the reasonable width and buried depth of the unloading board in this paper. The tests are conducted with and without the unloading board, and different widths and buried depths of the unloading board are also considered. The findings show that, without the external load, the reasonable board width and buried depth are 0.70 times and 0.53 times the wall height. With the external load, the reasonable board width is 0.35 times the wall height, and the large board width cannot effectively reduce the deformation of rib pillars, and the reasonable board width is 0.60 times the wall height. When both the external load and board width are relatively small, the reasonable buried depth is 0.53 times the wall height. However, when the external load is large, the reasonable buried depth is 0.70 times the wall height. The results also show that the setting of the unloading board effectively suppresses the deformation of rib pillars and controls the maximum deformation within an allowable range of the specification.